2010
DOI: 10.3109/17453674.2010.487241
|View full text |Cite
|
Sign up to set email alerts
|

Reduced morphine consumption and pain intensity with local infiltration analgesia (LIA) following total knee arthroplasty

Abstract: Background and purposePostoperative pain is often severe after total knee arthroplasty (TKA). We investigated the efficacy of the local infiltration analgesia (LIA) technique, both intraoperatively and postoperatively.Methods48 patients undergoing TKA were randomized into 2 groups in a double-blind study. In group A, 400 mg ropivacaine, 30 mg ketorolac, and 0.5 mg epinephrine were infiltrated periarticularly during operation. In group P, no injections were given. 21 h postoperatively, 200 mg ropivacaine, 30 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
186
0
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(202 citation statements)
references
References 20 publications
4
186
0
6
Order By: Relevance
“…A notable difference between these two studies was the intraoperative infiltration of the posterior capsule in both the injection and nerve block groups in the study by Carli et al [8]. When comparing studies using intraarticular injection after closure of the capsule with intraoperative periarticular injection, unlike pain scores that were generally more favorable with the periarticular injections, narcotic consumption was usually lower in both intraarticular and periarticular injection studies, although the difference tended to be greater for periarticular injections [5,6,12,19,27,36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A notable difference between these two studies was the intraoperative infiltration of the posterior capsule in both the injection and nerve block groups in the study by Carli et al [8]. When comparing studies using intraarticular injection after closure of the capsule with intraoperative periarticular injection, unlike pain scores that were generally more favorable with the periarticular injections, narcotic consumption was usually lower in both intraarticular and periarticular injection studies, although the difference tended to be greater for periarticular injections [5,6,12,19,27,36].…”
Section: Discussionmentioning
confidence: 99%
“…The use of combined sciatic and femoral nerve blocks over femoral nerve block alone has been shown to have improved pain scores and seems more beneficial for pain management [1,10,17]. When comparing intraoperative periarticular injections with intraarticular injections given after closure of the capsule, better pain scores are generally found in studies using periarticular injections [12,15,30,36]. With the exception of a few studies showing minimal improved pain [24,32], the majority of studies using intraarticular injections showed no improvement in pain scores postoperatively [3,5,15,19,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wound catheters can be used to deliver additional local anaesthetic postoperatively [3] and allow analgesia to be extended beyond 24 h [4][5][6][7][8]. Despite the increasing popularity of such techniques, concerns have been expressed regarding the safety of injecting large volumes of local anaesthetic into knee joints during orthopaedic procedures [9].…”
Section: Introductionmentioning
confidence: 99%
“…From these we identified 12 eligible RCTs. [3][4][5][6][7][8][9][10][11][12][13][14] Inter-observer agreement for trial eligibility was good (kappa = 0.75; SE 0.053). Table I reports the characteristics of the included trials and the local anaesthetic protocols used in the trials.…”
Section: Trial Identification and Selectionmentioning
confidence: 98%